Rancangan Reklamasi Lahan pada Kegiatan Pasca tambang Bijih Nikel di PT Citra Lampia Mandiri Malili - Fauziah Fauziah; Muhlis Muhlis; Muhtar Muhtar; Fatmawati Fatmawati; Rakhmad Armus (KOLONI, 2023)
The contribution of the mining sector to forest destruction in Indonesia has reached 10% and is now increasing every year to reach 2 million ha. Efforts to improve ex-mining land is by reclamation. The purpose of this study is to determine the design of reclamation activities and to evaluate the success of reclamation at PT. Citra Lampia Mandiri. The research method used is descriptive method with data collection techniques that are participant observation. Reclamation activities are carried out in several stages and activities that are systematic and well planned which have links between one activity and another in an effort to improve land quality. To determine the success rate of reclamation by providing an assessment of each reclamation activity, namely land use and revegetation, erosion and sedimentation control, top soil management, revegetation activities and plant maintenance. The results of the evaluation of the success rate of reclamation at PT. Citra Lampia Mandiri is 83% with good description.